Market simulation as a vehicle for peer-mediated whole-number construction in grade 2 - Sari Mawarni; Ryan Dwi Puspita (PPG IKIP Siliwangi, 2026)
This study explores how Grade 2 students construct the concept of whole numbers through a market simulation at SDN Citra Indah Sukamaju. The research was driven by students’ difficulties in understanding the abstract nature of place value. Using a qualitative descriptive design, data were collected through a preliminary cognitive diagnostic assessment, participatory observations, project rubrics, and student feedback. The results demonstrate that the market simulation created an authentic learning environment characterized by active student engagement in contextual problem-solving without teacher dominance, thereby fostering intensive social interaction. Based on the initial diagnostic assessment, 12 students (33.3%) who successfully answered higher-order thinking skills (HOTS) questions were identified as More Knowledgeable Others (MKOs) and provided essential peer scaffolding. Consequently, 24 students (66.7%) within the Zone of Proximal Development (ZPD) engaged in collaborative negotiations and showed measurable improvements in conceptual understanding through task completion. These findings suggest that the simulation provides an interactive pathway to support peer scaffolding and strengthen students’ conceptual understanding of whole numbers, rather than serving as a means of tracking formal developmental shifts.